Attitude towards Blended Learning, Stress Levels, and Academic Procrastination Behavior: A Cross-Sectional Study - Rania Azaria Triswiandi; Agneta Irmarahayu; Nunuk Nugrohowati; Hikmah Muktamiroh (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Academic procrastination can affect the quality of education. Normal stress reduces the likelihood of procrastination by 78% compared to very severe stress.   Abstract Introduction: Academic procrastination is the tendency to postpone academic work and is almost always associated with anxiety, which can adversely affect academic performance. This study aimed to determine the relationships between attitudes towards blended learning, stress levels, and academic procrastination behavior among medical students. Methods: This study employed an observational, analytical approach with a cross-sectional design and proportional stratified random sampling. The sample of this study comprised 229 students across 3 batches. The research instrument included an attitude questionnaire on blended learning, the Depression, Anxiety, and Stress Scale-21 Items (DASS-21), and an academic procrastination scale. The statistical tests used for bivariate analysis were the Chi-square and Kruskal-Wallis tests, with p-values reported. Multivariate analysis used ordinal logistic regression. Results: The bivariate test showed that the p-value for the association between attitudes towards blended learning and academic procrastination behavior was 0.612, and the p-value for the association between stress levels and academic procrastination behavior was 0.002. The multivariate test showed that normal stress reduced the likelihood of procrastination by 78% compared to very severe stress. There was no relationship between attitudes towards blended learning and academic procrastination, but there was a relationship between stress levels and academic procrastination. Conclusion: Attitudes towards blended learning did not affect academic procrastination behavior, while normal stress reduced the likelihood of procrastination compared to very severe stress.